BREAKFAST HABITS AND NUTRIENT ADEQUACY LEVEL OF SNACKS IS CORRELATED WITH NUTRITION STATUS AMONG ADOLESCENT IN SMPN 1 TUBAN - Chandramanda Dewi Damara; Lailatul Muniroh (Media Gizi Indonesia, 2021)
Adolescent often skip breakfast, so snacks are usually used as substitute for breakfast at school. Some snacks have unbalanced nutrient content. An imbalance in nutrient intake can affect nutritional status of adolescents. The purpose of this study was to analyze correlation between breakfast habits and nutrition adequacy level of snack with nutritional status of adolescents. The study design used in this study was cross sectional. The sampling technique was proportional random sampling with total sample of 77 students. Data on breakfast habits were obtained through questionnaires, while data on the adequacy level of snacks intake was obtained through 2x24 hours food recall. The correlation test used was spearman correlation. The results showed that there were correlation between breakfast habits, the adequacy level energy, protein, fat, and carbohydrate of snacks with nutritional status. Adolescent with poor breakfast habits and high adequacy of nutritional levels of snacks tend to have more obesity nutritional status.